1985
DOI: 10.1002/1098-108x(198502)4:1<71::aid-eat2260040108>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Body size distortion in bulimia nervosa

Abstract: Body size estimation was studied in normal weight women with bulimia nervosa and a matched group of normal controls in order to determine whether bulimia nervosa patients overestimate their body size and whether they do so to a greater degree than women who are not suffering from an eating disorder. Estimation of five body locations was measured objectively with adjustable markers. Percentage of over‐ or underestimation was determined by the ratio of estimated to actual body size. Relative to control subjects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…On image distortion, three studies found overestimation (Gleghorn, et al, 1987;Collins, et al, 1987;Lindholm & Wilson, 1988), one (Freeman, et al, 1985) found it to be present only in those without a history of anorexia nervosa, and one did not find any difference (Huon & Brown, 1986). On the analogue technique, three studies found overestimation (Norris, 1984;Willmuth, Leitenberg, Rosen, Fondacaro, & Gross, 1985;Gleghorn, et al, 1987), one did not (Birtchnell,Lacey,& Harte,3985), whereas one found it only in those without a history of being underweight , a finding contrary to that reported by Freeman et a1 (1985) using a different technique. One study using image marking found overestimation in bulimics (Gleghorn, et al, 1987), and the same study using a kinesthetic technique also found overestimation in the patients.…”
Section: Do Bulimics Overestimate More Than Controls?mentioning
confidence: 99%
“…On image distortion, three studies found overestimation (Gleghorn, et al, 1987;Collins, et al, 1987;Lindholm & Wilson, 1988), one (Freeman, et al, 1985) found it to be present only in those without a history of anorexia nervosa, and one did not find any difference (Huon & Brown, 1986). On the analogue technique, three studies found overestimation (Norris, 1984;Willmuth, Leitenberg, Rosen, Fondacaro, & Gross, 1985;Gleghorn, et al, 1987), one did not (Birtchnell,Lacey,& Harte,3985), whereas one found it only in those without a history of being underweight , a finding contrary to that reported by Freeman et a1 (1985) using a different technique. One study using image marking found overestimation in bulimics (Gleghorn, et al, 1987), and the same study using a kinesthetic technique also found overestimation in the patients.…”
Section: Do Bulimics Overestimate More Than Controls?mentioning
confidence: 99%
“…Perhaps not surprisingly, the resulting findings have been mixed. Whereas some studies have indicated that bulimics show distinctive patterns of body image distortion or dissatisfaction (e.g., Freeman, Thomas, Solyom, & Koopman, 1985;Willmuth et al, 1985), others (e.g., Birtchnell et al, 1985;Huon & Brown, 1986) have not. Cooper and Taylor (in press) have argued that studies of body image estimation that have not included a control population are uninterpretable because subjects' responses are easily influenced by specific procedures in the testing situation (e.g., the degree of image distortion possible, size of TV screen, and experimental instructions).…”
mentioning
confidence: 99%
“…Not one of the eight studies of Cooper and Taylor's (in press) analysis selected restrained eaters as normal controls. Indeed, Willmuth et al (1985) selectively screened-out highly restrained subjects, and Birtchnell et al (1985) omitted dieters. Excluding highly restrained but nonbulimic women from studies of bulimia tends to downplay the normative discontent with body size and shape (Striegel-Moore, Silberstein, & Rodin, 1986) against which the clinical disorder must be seen.…”
mentioning
confidence: 99%
“…In recent years, the phenomenon has also been found to occur with bulimic populations (Willmuth, Leitenberg, Rosen, Fondacaro, & Gross, 1985). In fact, some evidence suggests that bulimics may overestimate to a greater extent than individuals with anorexia nervosa (Thompson, Berland, Linton, & Weinsier, 1986).…”
mentioning
confidence: 99%